Identification and molecular mechanisms of novel antioxidative peptides from fermented camel milk (Kachchi breed, India) with anti‐inflammatory activity in raw macrophages cell lines. (14th October 2022) - Dharmisthaben, Patel; Sakure, Amar; Liu, Zhenbin; Maurya, Ruchika; Das, Sujit; Basaiawmoit, Bethsheba; Kumari, Reena; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Gawai, Kunal M.; Baba, Waqas N.; Maqsood, Sajid; et al.
Abstract : The investigation was aimed at assessing anti‐inflammatory and antioxidative activities along with the release of peptides with antioxidative properties during the fermentation of camel milk by Lacticaseibacillus casei (NK9). Reverse‐phase high‐performance liquid chromatography (RP‐HPLC) was used to separate the bioactive peptides of 3 and 10 kDa (permeates and retentates). Reverse‐phase liquid chromatography–mass spectrometry (RPLC/MS) was used to identify and characterise the pure bioactive peptides, and the effect of fermented camel milk on inflammation produced by lipopolysaccharide (LPS)/endotoxin in RAW 264.7 (Ralph and William's cell line) was also examined. Furthermore, docking revealed that peptides (LLNEK and IYTFPQPQSL) were predicted to inhibit myeloperoxidase (nMPO) activity by engaging with different residues in and around the human myeloperoxidase (hMPO) active site. Antioxidative peptides from camel milk fermented with Lactobacillus :